Evaluation of the total antioxidant capacity of flavored water and electrochemical purine damage by sulfate radicals using a purine-based sensor - Barroso, M. Fátima (2013)
In this study, a method for the electrochemical quantification of the total antioxidant capacity (TAC) in beverages was developed. The method is based on the oxidative damage to the purine bases, adenine or guanine, that are immobilized on a glassy carbon electrode (GCE) surface. The oxidative lesions on the DNA bases were promoted by the sulfate radical generated by the persulfate/iron(II) system. The presence of antioxidants on the reactive system promoted the protection of the DNA bases immobilized on the GCE by scavenging the sulfate radical. Square-wave voltammetry (SWV) was the electrochemical technique used to perform this study. The efficiencies of five antioxidants (ascorbic acid, gallic acid, caffeic acid, coumaric acid and resveratrol) in scavenging the sulfate radical and, therefore, their ability to protect the purine bases immobilized on the GCE were investigated. These results demonstrated that the purine-based biosensor is suitable for the rapid assessment of the TAC in flavors and flavored water.